2021
DOI: 10.3389/fpsyg.2021.674694
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a 3-Minute Mindfulness Intervention, and the Mediating Role of Maximization, on Critical Incident Decision-Making

Abstract: ObjectiveIn this study, we extend the impact of mindfulness to the concept of least-worst decision-making. Least-worst decisions involve high-uncertainty and require the individual to choose between a number of potentially negative courses of action. Research is increasingly exploring least-worst decisions, and real-world events (such as the COVID-19 pandemic) show the need for individuals to overcome uncertainty and commit to a least-worst course of action. From sports to business, researchers are increasingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…These findings have been demonstrated in robust randomised controlled trials and supported by meta-analyses (De Vibe et al, 2013;Regehr et al, 2013;Bamber and Kraenzle Schneider, 2016;Dvořáková et al, 2017;Bamber and Morpeth, 2018;Chi et al, 2018;Ma et al, 2019). The evaluation of online MBIs is in its infancy; however, recent meta-analyses found encouraging results for stress reduction (Spijkerman et al, 2016), as well as MBIs that are self-guided (Cavanagh et al, 2014;Ma et al, 2018) and brief, such as three (Shortland et al, 2021) and five minute (Howarth et al, 2019) interventions administered once.…”
Section: Introductionmentioning
confidence: 76%
“…These findings have been demonstrated in robust randomised controlled trials and supported by meta-analyses (De Vibe et al, 2013;Regehr et al, 2013;Bamber and Kraenzle Schneider, 2016;Dvořáková et al, 2017;Bamber and Morpeth, 2018;Chi et al, 2018;Ma et al, 2019). The evaluation of online MBIs is in its infancy; however, recent meta-analyses found encouraging results for stress reduction (Spijkerman et al, 2016), as well as MBIs that are self-guided (Cavanagh et al, 2014;Ma et al, 2018) and brief, such as three (Shortland et al, 2021) and five minute (Howarth et al, 2019) interventions administered once.…”
Section: Introductionmentioning
confidence: 76%
“…There are also several further questions to be explored. For example, recent research has shown that individual differences in personality characteristics (e.g., maximization) impact the degree to which decision-making is impacted by interventions (Shortland et al, 2021). As such, it is viable to propose that individual differences in certain key personality traits may moderate the effect of power on avoidance.…”
Section: Discussionmentioning
confidence: 99%
“…Then, participants were randomly assigned to either a three-minute LKM intervention or a control condition. The 3-minute dosage and design of the LKM intervention were chosen to reduce participant burden based on previous studies using brief meditation interventions [ 25 , 33 ]. In the LKM condition, participants were instructed to write a message to their recipient (close other or stranger) showing concern about the stigmatizing scenario and wishing them health, happiness, and wellbeing.…”
Section: Methodsmentioning
confidence: 99%